Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/wer.1633
|View full text |Cite
|
Sign up to set email alerts
|

Current available treatment technologies for saline wastewater and land‐based treatment as an emerging environment‐friendly technology: A review

Abstract: Different industrial activities such as agro‐food processing and manufacturing, leather manufacturing, and paper and pulp production generate highly saline wastewater. Direct discharge of saline wastewater has resulted in pollution of waterbodies by very high magnitudes. Consequently, an enormous number of pollutants such as heavy metals, salts, and organic matter are also released into the environment threatening the survival of human and biota. Saline wastewater also has significant effects on survival of pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 344 publications
0
3
0
Order By: Relevance
“…Garza and Kearney (2012) reported that methylene blue dye (MBD) in water at concentrations greater than 7 mg/kg can cause methemoglobinemia by direct oxidation while dosages higher than 15 mg/kg can generate hemolysis. Given the established and documented toxicity of MBD and other dyes, technologies for the removal of dyes from industrial effluents have been widely advocated in several approaches including filtration, photocatalysis, gel filtration, dialysis, etc (Marathe et al, 2021;Shahid et al, 2021). One of the most widely investigated and acceptable methods is the adsorption technique, which involves the use of suitable material with unique characteristics (adsorbent) to remove the dye (i.e adsorbate) through physisorption, chemisorption, or both mechanism (Eddy, 2010).…”
Section: Shells Based Cao Nanoparticles (Caonpo) Toward the Removal O...mentioning
confidence: 99%
“…Garza and Kearney (2012) reported that methylene blue dye (MBD) in water at concentrations greater than 7 mg/kg can cause methemoglobinemia by direct oxidation while dosages higher than 15 mg/kg can generate hemolysis. Given the established and documented toxicity of MBD and other dyes, technologies for the removal of dyes from industrial effluents have been widely advocated in several approaches including filtration, photocatalysis, gel filtration, dialysis, etc (Marathe et al, 2021;Shahid et al, 2021). One of the most widely investigated and acceptable methods is the adsorption technique, which involves the use of suitable material with unique characteristics (adsorbent) to remove the dye (i.e adsorbate) through physisorption, chemisorption, or both mechanism (Eddy, 2010).…”
Section: Shells Based Cao Nanoparticles (Caonpo) Toward the Removal O...mentioning
confidence: 99%
“…In a study from Hunter River in New South Wales, the indiscriminate discharge of saline wastewater from different sources (drainage, coal mines and power plants) to the natural water bodies deteriorated the water quality and aquatic diversity [17]. Due to the surface runoff of saline wastewater, drinking water is affected, resulting in an increase in sodium and sulfates in the freshwater, thus implying community health and socio-economic implications [18].…”
Section: Pickled Mustard Tuber Wastewater's Environmental Effectsmentioning
confidence: 99%
“…With the development of society and industrial progress, high-salinity organic wastewater, which refers to the organic wastewater with salt content higher than 1%, 1 is increasingly discharged from many industrial sectors such as chemical product manufacturing, food-processing industry, leather industry, petroleum industry and dyeing industry. 2 The discharge of high-salinity organic wastewater without treatment will adversely affect the aquatic life, ecosystems and agriculture. 3 Thus, high-salinity organic wastewater treatment has recently become a worldwide environmental concern.…”
Section: Introductionmentioning
confidence: 99%